Gender differences in health-related quality of life after coronary bypass surgery: results from a 1-year follow-up in propensity-matched men and women - Kendel, Friederike; Dunkel, Anne; Müller-Tasch, Thomas; Steinberg, Kerstin; Lehmkuhl, Elke; Hetzer, Roland; Regitz-Zagrosek, Vera (Psychosomatic medicine, 2011)
Objective: To examine whether the predictive value of gender for health-related quality of life (HRQoL) is independent of clinical health status and depression. Women undergoing coronary bypass surgery generally report a poorer HRQoL than men. - Methods: A total of 990 (20% women) patients completed study questionnaires 1 day before coronary bypass surgery and 1 year after surgery. Physical aspects of HRQoL were assessed with the Short Form 36 Health Survey. Depression was measured with the self-reported Patient Health Questionnaire. Propensity score matching was applied to match men and women with respect to 65 clinical variables. Of 198 women, 157 (79.3%) could be matched to a partner, resulting in an excellent balance of clinical variables between the matched groups. - Results: At baseline, propensity-matched men and women differed in physical functioning (p < .001) and role functioning (p = .007), but not in bodily pain and general health perception. In both men and women, HRQoL outcomes improved over 1 year. Preoperative depression predicted worse physical HRQoL in all outcomes, except general health perception 1 year after surgery. After adjusting for depression, gender lost its predictive power with respect to physical functioning. However, compared with women, men still reported a better role functioning. - Conclusion: Our data suggest that gender is a marker for role functioning, independent of the clinical health status and depression. Rehabilitation measures designed for the specific needs of women might help to improve their HRQoL.